Ikonoklasten Paulus? Fra billednegation til billedrestitution i Første Thessalonikerbrev - Lederballe Pedersen, Thomas (Periskop – Forum for kunsthistorisk debat, 2023)
This article deals with the first letter written by the apostle Paul, known as the First Letter to the Thessalonians (c. 50 CE), suggesting that by reading the letter as a document in the history of visuality as well as religious statement, it testifies to a dialectic within Paul’s theological anthropology. For the new Christians, Paul advocates the abolishment of cult images, which were ubiquitous in the Roman empire. But concurrent to his iconoclastic argument is an insistence on the members of the Thessalonian church taking on the role as religiously informed images themselves. Thereby, the letter shows Paul’s negative, iconoclastic attitude towards images being contradicted dialectically by the reemergence of an alternative type of image within the very same religious community instructed to disavow religious imagery. The article thus aims to situate the contents of the letter within the visual culture of the Roman empire, drawing on both textual evidence and images expressing the cultural patterns in question.